Low-cost beekeeping - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
An original beehive was developed in Senegal nearly 15 years ago. The entire design is focused on the cost of the hive and the special conditions of tropical apiculture. It is very different to imported modern hives but is no less effective....